Configuration and stability of naturally occurring all-cis-tetrahydrofuran lignans from Piper solmsianum. Issue 74 (4th October 2017) - Ramos, Clécio S.; Linnert, Harrald V.; de Moraes, Marcilio M.; do Amaral, João H.; Yamaguchi, Lydia F.; Kato, Massuo J.
Abstract : First occurrence of all- cis hexamethoxy-tetrahydrofuran lignans1a and1b, which are 6.5 kcal mol −1 less stable than the all- trans isomer grandisin (2a ). Abstract : The study of variability of the tetrahydrofuran lignan (−)-grandisin in leaves of Piper solmsianum (Piperaceae) revealed two unknown compounds, that were isolated and determined to be the all- cis tetrahydrofuran lignans1a [rel-(7 R, 8 S, 7′ S, 8′ R )-3, 4, 5, 3′, 4′, 5′-hexamethoxy-7, 7′-epoxylignan] and1b [rel-(7 R, 8 S, 7′ S, 8 R ′)-3′, 4′-methylenedioxy-3, 4, 5, 5′-tetramethoxy-7, 7′-epoxylignan]. Their structures were determined by spectroscopic analysis including 1D and 2D-NMR while their configurations were determined by ECD associated to the density functional theory (DFT) at the B3LYP/6-31G(d, p) level. The hydrogen bonds between methoxy groups in trimethoxyphenyl rings stabilizes the all- trans tetrahydrofuran lignan grandisin by 6.5 kcal mol −1 as compared to the corresponding all- cis isomer of grandisin. The occurrence of all- cis tetrahydrofuran lignans as natural products is a very rare event.